Synthesis and Characterization of Salamo-Type Bisoxime Compounds Bearing Nitro Group - Li, Gang; Wang, Li; Yang, Yu-Hua; Zhao, Meng-Meng; Zhang, Yu-Jie (Asian Journal of Chemistry, 2013)
A series of nitro salamo-type bisoxime compounds have been synthesized from 2-hydroxy-5-nitrobenzaldehyde and 1,6-bis(amino-oxy)hexane, 1,7-bis(aminooxy)heptane, 1,8-bis(aminooxy)octane or 1,10-bis(aminooxy)decane in ethanolic medium, respectively and characterized by elemental analyses as well as by IR, UV-visible and 1H NMR spectroscopy. Salamo-type bisoxime compound is much more useful to assemble supramolecular systems than a Salen moiety.